Saung Moderasi Dalam Membangun Komitmen Kebangsaan Dan Toleransi Pada Lembaga Pendidikan Di Kelurahan Pendahara, Kecamatan Tewang Sangalang Garing - Yeni Sulistiawati; Agus Fitrah Lianor; Sisil Lia Nur Safitri; Aisyah Aisyah; Dedong Dedong; Intan Nisful Laila; Indra Triwijaya; I Gede Purna Wijaya; Desta Natalia; Oktari Oktari (FKIP, Universitas Palangka Raya, 2023)
Pendahara Village is one of Tewang Sangalang Garing Subdistrict with religious diversity. The existence of school institutions at various levels is a strategic place to regarding a life of moderation through national commitment and tolerance. Pendahara Village can produce superior human resources in the lives of religious communities. There is a need to empower the Pendahara community through educational institutions in Pendahara Village. It is hoped that Saung Moderasi can encourage all components of school institutions in community life to increase national commitment and tolerance as a region that is Bhinneka Tunggal Ika and known to the wider community. This community service activity aims to determine the effectiveness of implementing Saung Moderation in increasing national commitment and tolerance through educational institutions in Pendahara Village. This research uses the Participatory Action Research (PAR) method. The result of this service is that Saung Moderasi activities contribute to Pendahara Village through educational institutions to build national commitment and tolerance in community life.